2022
DOI: 10.1002/advs.202200737
|View full text |Cite
|
Sign up to set email alerts
|

Chloroform‐Assisted Rapid Growth of Vertical Graphene Array and Its Application in Thermal Interface Materials

Abstract: With the continuous progress in electronic devices, thermal interface materials (TIMs) are urgently needed for the fabrication of integrated circuits with high reliability and performance. Graphene as a wonderful additive is often added into polymer to build composite TIMs. However, owing to the lack of a specific design of the graphene skeleton, thermal conductivity of graphene-based composite TIMs is not significantly improved. Here a chloroform-assisted method for rapid growth of vertical graphene (VG) arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…After the liquid metal gallium was further modified on the VAGM surface as the cap layer, the resultant LM-VAGM exhibits a slightly lower κ ⊥ of 176 W m −1 K −1 compared to that of VAGM. Nevertheless, this thermal conductivity achieved is still higher than that of most thermally conductive materials based on various vertical structures reported so far, including vertically aligned metal nanowires [39,40], carbon fibers [41], carbon nanowires [42][43][44][45], graphene nanowalls [33,36,37], and graphene monolith [24,26,27,30,32], as shown in Fig. 3b and Table S1.…”
Section: Thermally Conductive Performance Of Lm-vagmmentioning
confidence: 74%
See 1 more Smart Citation
“…After the liquid metal gallium was further modified on the VAGM surface as the cap layer, the resultant LM-VAGM exhibits a slightly lower κ ⊥ of 176 W m −1 K −1 compared to that of VAGM. Nevertheless, this thermal conductivity achieved is still higher than that of most thermally conductive materials based on various vertical structures reported so far, including vertically aligned metal nanowires [39,40], carbon fibers [41], carbon nanowires [42][43][44][45], graphene nanowalls [33,36,37], and graphene monolith [24,26,27,30,32], as shown in Fig. 3b and Table S1.…”
Section: Thermally Conductive Performance Of Lm-vagmmentioning
confidence: 74%
“…Finally, the recently emerging direct growth of vertical graphene arrays 1 3 by plasma-enhanced chemical vapor deposition (PECVD) is also an effective method for preparing vertically aligned graphene-based TIMs [33][34][35]. Xu et al demonstrated that the resultant TIM obtained by adding 8.6 wt% vertical graphene arrays to PDMS has a κ ⊥ of 34.3 W m −1 K −1 with good compressibility [36]. Based on the above progress, various vertically aligned graphene-based TIMs reported so far have made great breakthroughs in κ ⊥ compared with conventional TIMs, but their actual heat dissipation efficiency cannot still meet expectations in the packaging conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the low-concentration carbon source system, due to less amorphous carbon during VG growth, the hydroxyl radicals generated by a large amount of water will dilute the active carbon radicals, then inhibit the growth of VG and introduce some defects in VG sheets. Figure 3e and Figure S6, Supporting Information, show there is a linear relationship between the height of VG arrays and growth time, more importantly VG arrays at a height of 144 µm are prepared within 10 h. [32][33][34][35][36][37][38][39][40] Figure S7, Supporting Information, shows that the sheet resistance of VG arrays gradually decreases and tends to be stable with the increase of growth time, and Figure S8, Supporting Information, reveals an obvious disparity of surface wettability between VG glass and bare glass. Further, the contact angle values show a gradual increase with the extension of CVD growth time and reaching 149.2° for 60 min growth.…”
Section: The Effect Of Watermentioning
confidence: 94%
“…Efficient thermal management is one of the most critical technical challenges in emerging high power density electronics and energy storage devices. [1][2][3] World-wide efforts have been made to make electronic devices and systems achieve high computing speed, increased integration densities, and smaller and thinner appearance for decades. [4][5][6] Integration upgrades lead to sharply increased power densities and internal heat uxes, which puts forward a higher demand on the timely dissipation of excess heat from hot spots to the external environment.…”
Section: Introductionmentioning
confidence: 99%